Loose Parts Media Learning Management to Improve Linguistic Skills in Non-Formal Early Childhood Education Institutions in Wonosobo District, Wonosobo Regency - Afif, Fuad Khoirul; Mawardi, Imam; Imron, Imron (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the effect of learning management with loose parts media on improving the linguistic abilities of children aged 5-6 years in non-formal PAUD institutions throughout Wonosobo District. This research, conducted in a non-formal PAUD institution in Wonosobo District, used a qualitative descriptive method to explore the impact of loose parts media on the logical and linguistic intelligence of children aged 5-6 years. Data was collected through direct observation, structured interviews, and documentation, focusing on children's interactions with loose parts and teachers' responses to this learning method. The analysis involved data reduction, presentation, and conclusion drawing, with the findings expected to enhance future learning methods. This study found that children aged 5-6 years in Non-Formal PAUD, Wonosobo District, can express their desires and dislikes through speaking skills, with language development indicators including understanding commands and repeating complex sentences. The application of loose parts in learning management significantly enhances their linguistic abilities, as demonstrated by positive outcomes in one well-implemented institution. However, challenges such as limited funding and lack of training information hindered broader implementation. To address these, it is suggested that BOSP funds be allocated for materials and educator training